The use of imagery by rowers - Barr, K.; Hall, C. (International Journal of Sport Psychology, 1992)
Rowers of all levels (N = 348) were assessed on the Imagery Use Questionnaire. A variety of findings indicated different uses of imagery across the sample performance levels. 1. The use of imagery increased just prior to competition. 2. Internal imagery was used more than external ("visualization") imagery. 3. "Feel" (i.e., kinesthetic cues) was an important aspect of the imagery. 4. Elite rowers reported feeling their blade, muscles, parts of the stroke, and the boat and its action in the water more often than novices. 5. Elite rowers reported more structured and regularity in use of imagery. 6. Novices included more errors and incorrect rowing than elites. 7. Elites used imagery as a way of practicing pre-race routines. Implication: Imagery appropriate for competition preparation needs to be taught and practiced in a manner that can be transferred exactly to competition settings. A concentration on accurate and successful content is crucial.